Cartographic analysis of tourist attractive regions using GIS technologies - Lepetiuk, Viktoriia (Geodesy and Cartography, 2020)
In this article, I compare cartographic methods that can be used for analyzing tourist attractive regions and explore the possibilities of using GIS technologies for such analysis. I provide a specific methodology of searching for the most attractive tourist regions using Voronoi diagrams and heatmaps. I demonstrate the methodology by applying it to certain types of tourist resources in Chernihiv region of Ukraine.